Retrospective of IKN Nusantara Investment; Study of Apple Investment Curtailment: Technostructure of Indonesia and Vietnam - HEPTARIZA, Anita; DARMAWAN, Andreas James; SIHWINARTI, Dwi; RAMAYU, I Made Satrya; ERAWATI, Kadek Nonik (PT Keberlanjutan Strategis Indonesia, 2024)
In the government's efforts to collect investment in IKN (National Capital City) Nusantara in Indonesia, technostructure; or advanced technological infrastructure is one of the crucial factors in attracting investment from global technology companies, but Indonesia still faces significant challenges in technostructure readiness compared to countries such as Vietnam, reflecting on the investment selection of technology company Apple. This study aims to analyze the current state of Indonesia's technostructure, compare it with Vietnam, and formulate what strategic steps are needed by the Indonesian government to develop a better technostructure in the next three decades. Using a descriptive qualitative method, this study collects purposive sampling-based data through literature studies, documentation, and other supporting data to provide an in-depth understanding of the technostructure conditions of the two countries. The discussion includes a detailed analysis of the state of Indonesia's technostructure and the challenges it faces. Then the study continues by comparing the technostructure readiness of Indonesia and Vietnam to highlight the strengths and weaknesses of each country, and the final stage details the strategic steps that the Indonesian government must take in the next three decades to achieve competitive technostructure readiness in Indonesia. This study concludes that it is important for Indonesia to accelerate the development of technostructure to increase the attractiveness of global technology investment, especially with open management.